Genetic structure of natural populations of Cryptocarya aschersoniana Mez (Lauraceae) through isozyme markers - Moraes, Pedro Luís Rodrigues de; Derbyshire, Maria Teresa Vitral de Carvalho (Biota Neotropica, 2002)
Through the analysis of 39 polymorphic allozyme loci, allele frequencies were estimated from 267 individuals of 12 natural populations of Cryptocarya aschersoniana native to "Planalto forests" of the state of São Paulo and south of Minas Gerais, Brazil. Estimates of Wright's F statistics were computed through the analysis of variance for obtaining unbiased estimation of corresponding parameters F=F IT, θ P =F ST and f=F IS. Average values of F^ were 0.552 < 0.415 < 0.275; those of θ^P were 0.395 < 0.335 < 0.279; and those of f^ were 0.292 < 0.119 < -0.039. These results indicated that individuals within populations might be panmitic, and that the diversity among populations was fairly high, being superior to what would be expected for groups of plants having a full-sib family structure. From estimates of θ^P obtained for populations taken two at a time, the model of isolation by distance was employed and it has shown to be inadequate for explaining the divergence found among populations. The estimated gene flow of 0.4 migrants per generation corroborated the pronounced populational differentiation. Due to negligible fˆ @ F^IS values found, the variance effective size for each population was equivalent to its sampling number. Under a metapopulation context, considering the 12 populations sampled for the species, the effective population size was 15.4 individuals (5.77%) for the total sampled, indicating that sampling of different populations should be an important strategy for their management.